Laboratorio de investigación y difusión de bioenergías: infinity bioenergy - master Plan Raíz Verde Bogotá – Sibaté (2018)
The work proposes research and management spaces that seek to train farmers and professionals from the region of the Soacha province, in the development of ways to implement renewable energies in rural and urban areas, which benefit the community socially, economically and environmentally, to the present environmental pollution especially in the hydric and air tributaries, the scarcity of energy caused by the exponential increase of the population in the region and the collapse of the sanitary landfills, since there are no processes of purification of the garbage that in Most are organic waste that serve as fuels or fertilizers. For this reason it is implanted in this place as an articulating equipment of the municipalities of Soacha and Sibaté, that would work responding to the environmental, energetic and social needs of the region.